Assessment of status of solid waste management in Asella town, Ethiopia - Gorfnesh Lema; Million Getachew Mesfun; Amade Eshete; Gizachew Abdeta (BMC, 2019)
Abstract Background Improper solid waste management (SWM) is a major public health and environmental concern in the urban areas of many developing countries such as Asella Town. The aim of this study was to assess the status of SWM in Asella town. Methods A community-based cross-sectional study design was used to assess the status of improper SWM and associated factors in Asella town. From the total of eight kebeles (smallest administrative unit in Ethiopia) four kebeles were randomly selected using lottery method. The sample size was 413 households. The households were proportionally allocated to each randomly selected kebeles. The data was collected by pretested questionnaire in the local language. Data was entered using statistical software Epi Info version seven and transferred to SPSS version 21. Descriptive data analysis was done to summarize the socioeconomic status of the respondents. Chi-square was used to show the association between the status of solid waste management and different variables. Binary logistic regression was used to determine the potential factors for improper SWM. Result 332 (82.8%), had improper solid waste management practice. Lack of adequate knowledge about solid waste management and not having access to door to door solid waste collection could have contributed to the reported improper solid waste practice. Participants who didn't have access to door to door solid waste collection service were about three times more likely to practice improper solid waste management when compared to those who had access (AOR = 2.873, 95 CI (1.565,5.273) P = 0.001). Conclusion The study finding showed that, the majority of the residents practiced improper solid waste management. Lack of adequate knowledge about solid waste management and not having access to door to door solid waste collection could have contributed to the reported improper solid waste practice. Therefore, there is a need to enhance the awareness of the community about proper SWM and to improve the door to door solid waste collection service by the town municipality.